2022
DOI: 10.1039/d2tb01804g
|View full text |Cite
|
Sign up to set email alerts
|

Metal–phenolic networks acted as a novel bio-filler of a barrier membrane to improve guided bone regenerationviamanipulating osteoimmunomodulation

Abstract: Guided bone tissue regeneration membrane (GBRM) is traditionally viewed as an inert physical barrier to isolate soft tissue from bone defect area. However, as a “foreign body”, the implantation of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In contrast, M2-polarized macrophages produce various anti-inflammatory and pro-healing factors, which are beneficial for bone regeneration . Accumulative evidence has highlighted that biomaterials with immunomodulatory properties could orchestrate the sequential activation of macrophages to promote the rapid resolution of inflammation and guarantee the predominance of M2-polarized macrophages to launch a successful osseointegration process. …”
Section: Results and Discussionmentioning
confidence: 99%
“…In contrast, M2-polarized macrophages produce various anti-inflammatory and pro-healing factors, which are beneficial for bone regeneration . Accumulative evidence has highlighted that biomaterials with immunomodulatory properties could orchestrate the sequential activation of macrophages to promote the rapid resolution of inflammation and guarantee the predominance of M2-polarized macrophages to launch a successful osseointegration process. …”
Section: Results and Discussionmentioning
confidence: 99%
“…Then a few studies reported polyphenol‐Sr modified membranes or scaffolds, investigating their effect on the bone regeneration process or osteoarthritis. [ 37 , 38 ] The influence on the interfacial osseointegration around the implant surface remains unclear. Considering that MPN is biosafe and biodegradable in the physiological microenvironment, it is expected that TA‐Sr‐based MPN can offer an osteoimmunomodulation biointerface to improve the early integration of Ti implants.…”
Section: Introductionmentioning
confidence: 99%